KEBUGARAN FISIK ANAK USIA REMAJA PESERTA EKSTRAKURIKULER GAME E-SPORT UNTUK KEMAMPUAN FLEKSIBILITAS LEHER DI SMA HARAPAN DENPASAR - Yastika, Gede Esa; Sena, I Gede Arya; Daryono (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
This study aims to determine whether contract relaxation, stretching, and massage exercises can improve the neck flexibility of teenage children participating in E-Sport Game Extracurricular at Harapan Denpasar High School. This study used a pre-experimental method with a one-group pre-test and post-test design. The research sample consisted of 20 people selected based on exclusion and dropout. The Neck Disability Index (NDI) and Goniometer. This research was conducted 12 times in a meeting. The Shapiro-Wilk test was used to test the normality of the study's results, and the paired sample T-test was used to test the research hypothesis. Both the ROM and neck functional ability data were analyzed. Therefore, we can conclude that both the neck ROM data and neck functional ability follow a normal distribution. The paired-sample T test results for neck ROM and NDI of teenage children participating in extracurricular e-sports games show a significant value of 0.000. This indicates that the provision of Contract Relax Stretching and Massage is effective in improving neck flexibility. This is evidenced by an increase in the percentage of neck ROM flexibility values in active motion neck flexion samples, which increased by 9.9%, and in active motion neck extension samples, which increased by 11.5%. The percentage value of improvement in neck functional ability is 25%. Therefore, we can conclude that providing contract, relax, stretch, and massage exercises has increased neck flexibility.